Media - Migration - Integration European and North American Perspectives - Geißler, Rainer; Pöttker, Horst (Medienumbrüche, 2009)
Following economists and scientists, politicians of various European countries have realized that a modern society with a declining birthrate is in need of immigrants. What can journalists contribute, in order to enable migrants to feel at home in their receiving country? What can be missed and ruined by journalists and media with regard to the integration of ethnic minorities? Scholars from Austria, Canada, France, Germany, Russia, Switzerland, The Netherlands, and the U.S. present their findings on the matter of media integration of migrants. Can European media learn from experiences in the classic countries of immigration in North America?